Жадьылӥсь мешок: выжыкылъёс / Вениамин Ившин - Ившин Вениамин Никонорович (Удмуртия, 2012)
Экземпляры: 12 (20240216) / Инвентарный номер: 56619 / Цена: 20.00 / Авт.знак: И 25 / ГРНТИ: 17 / ББК: 84(2Рос=Удм)